2015
DOI: 10.1007/s00521-015-1944-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrating corporate governance and financial variables for the identification of qualified audit opinions with neural networks

Abstract: Prior studies have contributed to the development of models that help predict audit opinions, and have applied several methodologies in the search of better predictions. Nevertheless, and even though the existing literature on the prediction of audit opinions is profuse, the results achieved by the existing modelling are still considerably far from having obtained high levels of prediction, and the results are not in excess of 80 % in terms of classification. In previous research, prediction models of audit op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
(86 reference statements)
1
17
0
1
Order By: Relevance
“…◆ Different predictors are used. Most researchers use only financial metrics, but some use market data (Dopuch et al, 1987;Francis and Krishnan, 1999;, nonfinancial data, or latent constructs (Fernández-Gámez et al, 2016) as well. Even when nominally using the very same predictors, the calculations are likely to differ due to the differences in national reporting frameworks.…”
Section: Paper Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…◆ Different predictors are used. Most researchers use only financial metrics, but some use market data (Dopuch et al, 1987;Francis and Krishnan, 1999;, nonfinancial data, or latent constructs (Fernández-Gámez et al, 2016) as well. Even when nominally using the very same predictors, the calculations are likely to differ due to the differences in national reporting frameworks.…”
Section: Paper Sample Characteristicsmentioning
confidence: 99%
“…As a result, over the past decades, numerous models for predicting the type of audit opinion have been proposed in the literature (Kirkos et al, 2007). Earlier studies have mainly relied on the use of classical statistical modeling techniques, mainly probit and logistic regression models (Dopuch et al, 1987;Francis and Krishnan, 1999;, while more recent ones have shown an increased preference for modern machine learning techniques, such as decision trees and artificial neural networks (Fernández-Gámez et al, 2016;Pourheydari et al, 2012;Saif et al, 2013;Yasar et al, 2015). 1 Although the abundance of empirical research, conducted on the topic, might be expected to provide a solid basis for practitioners to identify a predictive technique that is best suited for predicting audit qualifications, we argue that this is not possible for two main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The present study uses 35 independent variables obtained from previous studies on audit opinion prediction models [1,2]. These independent variables are presented in Table 2.…”
Section: Variablesmentioning
confidence: 99%
“…Previous studies have developed models to predict audit opinion. Auditors can use these models to plan audit procedures, as a quality control tool in the stage of review of a commitment, and for the analysis of the variables that affect the probability of obtaining a qualified opinion [1,2]. The existing audit opinion prediction models have only been developed in the context of individual financial statements, and none have referred to consolidated financial statements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation